Constructing Professional Identity: Investigating Stress Factors and Resilience Experienced by EFL Novice Teachers - Krismalita Sekar Diasti (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
Several studies show that EFL novice teachers often feel stress as they encounter shock from the rapid shift of a student to a teacher. Stress experienced by EFL novice teachers occurs because of internal or external factors. Stress which cannot be regulated will result in teacher burnout that can lead them to leave the profession. This qualitative study intended to investigate EFL novice teachers’ stress factors and coping strategies which influence their professional identity construction. The data was obtained by conducting an in-depth interview with three EFL novice teachers. The findings showed that EFL novice teachers experienced stress because of three factors, namely, personal, interpersonal, and organization factors. Despite feeling stress, EFL novice teachers demonstrated their abilities to cope with the circumstances. The participants elaborated how they cope with the situations as well as how stress factors influenced their identity as teachers. This study provides some suggestions for future researchers and EFL novice teachers.